Modalność epistemiczna w języku amharskim - Krzyżanowska, Magdalena (My University, 2020)
Celem rozprawy jest opis i analiza modalności epistemicznej we współczesnym języku amharskim, dominującym etiosemickim języku Etiopii. Modalność epistemiczną rozumie się jako ocenę przez mówiącego jej/jego niedostatecznej wiedzy w stosunku do propozycji. Badaniu zostało poddanych około 70 wyrażeń epistemicznych (epistemifikatorów) poklasyfikowanych na gramatyczne, leksykalne, łącznikowe (stanowiące kategorię pośrednią) i parentetyczne, podług stopnia ich gramatykalizacji/leksykalizacji. Epistemifikatory znacznie wykraczają poza grupę czasowników modalnych typu „móc, musieć, powinien”. Procedury badawcze zastosowane do analizy semantycznej wyrażeń epistemicznych to testy falsyfikacji/weryfikacji i substytucji, pojęcie wymiaru i cechy oraz metoda analizy zdań w terminach struktury tematyczno-rematycznej. Główne narzędzie ich opisu stanowi osiem wymiarów, skonstruowanych na potrzeby języka amharskiego, z których trzy mają charakter formalny, a pięć – semantyczny. W pracy zaproponowano również szkice semantyczne niektórych wyrażeń (zarówno gramatycznych jak i leksykalnych) oraz poddano bardziej szczegółowemu badaniu trzy typy zdań dopełnieniowych. Ostatnia część pracy poświęcona jest interakcji między modalnością epistemiczną a dwiema innymi, niemodalnymi kategoriami czasu i negacji. Korpus językowy wykorzystany w rozprawie został zaczerpnięty z tekstów pisanych i ustnych, które zostały zinterpretowane i przeanalizowane z pomocą amharskojęzycznych informatorów.

This thesis is devoted to a description and analysis of the category of epistemic modality in contemporary Amharic, the dominant Ethiosemitic language spoken in Ethiopia. Epistemic modality is understood as the speaker’s assessment of her/his non-knowledge in respect to the proposition. The thesis deals with 70-odd Amharic epistemic expressions (epistemificators) that have been classified into grammatical, lexical, copular (an intermediate category), and parenthetical, according to their degree of grammaticalization/lexicalization.The epistemificators go considerably beyond the simple concept of “modal verbs”. They were studied semantically by means of the following research procedures: tests of falsification/verification and substitution, the concept of epistemic dimensions and their values, and the analysis of sentences in terms of thematic-rhematic structure. The epistemic expressions are described primarily in terms of eight Amharic-specific dimensions, three formal and five semantic. In addition to the dimensional analysis, for selected epistemic expressions (both grammatical and lexical), prose semantic discussions are provided and, subsequently, three types of complement clauses are examined in greater detail. The final part of the thesis discusses the interaction between epistemic modality and two other categories, namely time and negation. The study is based on a corpus of written and spoken texts taken from both printed and electronic media, which have been interpreted and analyzed with the help of Amharic native-speaker informants.
Epistemic modality in Amharic
Wydział Neofilologii
Keywords: językoznawstwo; semantyka; wymiar; język amharski; modalność epistemiczna; linguistics; semantics; Amharic; epistemic modality; dimension